Pesantren dan Politik Lokal:: Jejak Koalisi Moral Dalam Kontestasi Elektoral di Wajo - Besse Sri Ratih; Muhammad Al Hamid; Andi Naharuddin (Center of Peace, Conflict and Democracy - Hasanuddin University, 2025)
As'adiyah Islamic Boarding School and PAN cadres have a close relationship because many alumni of the boarding school are cadres. Many PAN cadres hold important positions in the Wajo Parliament and even the position of Chairman of the PAN DPP is an alumni of Asadiyah Islamic Boarding School, so indirectly it will be easier to establish communication with alumni and students of Asadiyah who are members of PAN. PAN uses a political strategy by introducing students to actors according to religious teachings and conditions in Wajo. Through religious activities, PAN maintains relations with the boarding school, sometimes with financial and infrastructure support. In addition, the success of alumni students, and the position of actors with PAN containers labeled as religion is very profitable and is an extraordinary strategy that is not intentional. Through religious programs such as religious studies, preaching, and Friday sermons and other activities, it seems to be a strong communication and branding pattern and in line with PAN's position which is engaged in the religious field with the keywords